El Proyecto BEPS de la OCDE y el Derecho Fiscal Internacional en Brasil - Rocha, Sergio André (Pontificia Universidad Católica del Perú, 2016)
In this article, the author analyzes the BEPS project of the OECD and its implications in the International Tax Law of Brazil as a potential generator of a new stage in the international taxation. In that sense, he explains the Brazilian international policy, the context that led the signing of conventions and the model that was followed for it. Furthermore, he assesses the importance of the fiscal transparency and the exchange of information, aspects connected with the cooperation and competition.

En el presente artículo, el autor analiza el proyecto BEPS de la OCDE y sus implicancias dentro del Derecho Fiscal Internacional de Brasil, como el posible generador de una nueva etapa en la imposición internacional. En ese sentido, explica la política internacional brasilera, el contexto que motivó a la firma de Convenciones y el modelo que se siguió para el mismo. Asimismo, evalúa la importancia de la transparencia fiscal e intercambio de informaciones, conectado con las características de cooperación y competencia.
The BEPS Project of the OECD and the International Tax Law in Brazil
Keywords: Beps; Public International Law; Oecd; Brazilian Tax Policy; Beps; Derecho Internacional Público; Ocde; Política Fiscal Brasilera; https://purl.org/pe-repo/ocde/ford#5.05.00